Identifying Occupational Therapy Research Priorities in Trinidad and Tobago: A Group Concept Mapping Study - Savannah Murray-Mendes; Anastasia Raquel Martinez; Katie L. Hackett (Occupational Therapy International)
In Trinidad and Tobago, occupational therapy is an emerging profession with limitations in the number of practitioners and the scope of practice. With the development of a new Master of Science Occupational Therapy programme in the country, the profession is continuously growing. There has been an increased demand for culturally relevant research to build the occupational therapy evidence base locally. However, the narrow range of occupational therapy literature in the country makes it difficult to highlight research gaps and decipher what research areas should be prioritised to best impact occupational therapy practice at present. This group concept mapping study is aimed at identifying priority areas for occupational therapy research in Trinidad and Tobago from the perspectives of occupational therapy students and practitioners. Participants brainstormed and contributed specific research ideas they would like to see developed in the country. Individually, participants sorted these ideas into themes and rated each idea based on perceived importance and feasibility. Using the GroupWisdom™ software, multidimensional scaling and hierarchical cluster analyses were applied to the sort data to create idea clusters within a concept map. Rating values were analysed to determine priority research themes within the concept map. The resulting concept map illustrated seven research priorities: Contextualising Practitioner Development, The Realities of Emerging OT Practice, Localising Mental Health OT, Occupation and Participation of Children and Youth, School-based OT in the Local Context, OT with Special Populations, and OT Contributions to the Public Health Sector. These findings represent the research needs of the occupational therapy profession in Trinidad and Tobago and will help to focus future researchers’ efforts to expand the local evidence base.